Fundamental physics lecture program for enhancing mathematics model construction and graph representation skills - Kurniawan, Dede Trie; Suhandi, Andi; Kaniawati, Ida; Rusdiana, Dadi (AIP conference proceedings, 2022)
This study aims to test and see the effect of student models and worksheets developed in improving the construction skills of mathematical representation and graphics. In the procedure implementation, the quasi-experimental method was carried out with a pretest-posttest only control group design. In this experimental design, one control class is used, namely the class that carries out conventional lecture activities which are usually carried out in universities. The subjects of the research are 50 students of mathematics teacher candidate at one of Cirebon city private universities. The results of the product implementation test show that the use of the Physics-Oriented Course Program for Mathematical and Graphical Representation Construction (POCP-CMGR) has a strong effect on improving students' mathematical and graphic representation construction skills. The use has a high effectiveness in improving the construction representation ability. This good result is because the lecture program has a structured syntax and steps to train how to think and investigate and then communicate in the form of mathematical models and graphical representations that explain a physical phenomenon. Through this model shows the change of attitude of students of mathematics teacher candidates in viewing the relevance and urgency of basic physics for the fulfilment of competence of candidates for mathematics teachers.